Occurrence and species composition of shrimp postlarvae in three different waterbodies in Andhra Pradesh - Chinni, Satyavathi; Rao, Prabhakara; _, Yallapragada (Indian Journal of Fisheries, 2011)
Investigations were made on the occurrence and species composition of shrimp postlarvae in three different water bodies namely Gosthani estuary, Ghambeeragedda and Kakinada Bay of Andhra Pradesh. The occurrence of Penaeus monodon, P. indicus, P. semisulcatus, Metpenaeus monoceros, M. dobsonii, Macrobrachium rosenbergii and M. malcomsonii were noticed. Thespecies composition and abundance differed at all three stations and the peaks of abundance varied from species to species. The results of the present study indicated that these areas are important sources of postlarvae.